Metode Pembelajaran Bahasa Arab Konvensional dan Kontemporer (Analisis Komparatif) - Mahbubi, Abdillah (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
Purpose-. This research aims to determine conventional and contemporary Arabic language learning methods, as well as recommendations for teachers to use learning media. Design/Methodology/Approach- This research uses a qualitative descriptive method with a comparative analysis approach to compare conventional and contemporary Arabic language learning methods. Data collection uses literature reviews with references to scientific journals, books and relevant previous research. Findings- The research results show that there are many conventional and contemporary Arabic language learning methods. The methods displayed are grammatical and translation, audio lingual, direct, eclectic, communicative, and technology based learning (TBL) methods. All methods have their own characteristics, advantages and disadvantages. Teachers can choose learning methods that suit the conditions and material being taught. Research Limitation/Implications- The limitations of this research are that it focuses on conventional and contemporary Arabic language learning media with comparative analysis and is limited to a literature review where it goes to the field to collect data.